A RETROSPECTIVE COMPARATIVE ANALYSIS STUDY OF ANTERIOR AND POSTERIOR APPROACHES IN SHOULDER FUNCTION OUTCOMES IN BRACHIAL PLEXUS INJURY. - Sanjay Kumar; Ankita Jain; Dr. Ravi Bilunia (Student's Journal of Health Research, 2023)
Background:  Branchial plexus injuries are associated with shoulder dislocation and nerve damage. The transfer of the nerve from the spinal accessory nerve to the supracapsular nerve is the preferred mode of reviving the nerves. Posterior and anterior approaches can be applied for the same. The aim of this study is to compare the posterior and anterior methods and evaluate their outcomes Methods:  Data from 68 patients were studied retrospectively, and among them, 32 patients underwent surgery by anterior method and 36 patients underwent surgery by posterior surgery. Evaluation of the patient's rotation of motion and muscle power grading was done. Result:  The recovery of the patients with posterior surgery was earlier in the 6-month follow-up itself, and the difference was statistically significant. Whereas, when compared for 18 months, the difference in the grading of muscle and rotation of the motion was not statistically significant. Conclusion:  The recovery time was observed to be earlier in the posterior group as compared to the anterior group. However, when considering the 18-month follow-up period, the observed difference in recovery time between the two groups did not reach statistical significance. However, it is imperative to acknowledge the significance of the posterior approach in the context of clavicle injury and the associated impairment of the supravascular nerves. Recommendation: To obtain a better shoulder function, reinnervation of both the Suprascapular Nerve and Axillary Nerve is recommended.